Penerapan Media Ajar Berbasis Buku Cerita Bergambar untuk Meningkatkan Keterampilan Membaca Siswa Kelas IV di SDN 8 Pemenang Barat Tahun Ajaran 2023/2024 - Karunia, Bq. Ila; Muhajirin , Muhammad; Dwipa, Lalu Belik Made (Lembaga Bale Literasi, 2024)
This study aims to improve students' reading skills through the application of teaching media based on picture storybooks in class IV. This research was conducted at SDN 8 Pemenang Barat with a total of 20 students. This research is a classroom action research in which the researcher collaborates with the fourth grade teacher at SDN 8 Pemenang Barat. The object of this research used data collection techniques, interviews, observations, tests, and photo documentation. The data analysis techniques used were qualitative and quantitative techniques. This research can be said to be successful if it reaches the criteria for classical completeness of 80%. The results of the research conducted showed that there was an increase in the reading skills of grade IV students at SDN 8 Pemenang Barat after applying teaching media based on picture storybooks, it was proven that students' reading skills increased every cycle, namely in the pre-cycle at the level of reading student paragraphs were still very low with the classical completeness criteria being 0% or 20 of the students were not complete. In cycle I action, it increased to 30% or 6 out of 20 students were complete, in cycle II it increased to 60% or 12 out of 20 students were complete, and in cycle III it continued to increase which reached 85% or 17 out of 20 students were complete. This research was stopped in cycle III because it had reached the success criteria. So it can be concluded that the application of teaching media based on picture storybooks can improve student learning